2014
DOI: 10.1159/000362176
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Volume Index and Chronic Inflammation of the Prostate Type IV with Respect to the Risk of Prostate Cancer

Abstract: Background: Benign prostatic hyperplasia and prostate cancer (PCA) alter the normal growth patterns of zonal anatomy with changes of prostate volume (PV). Chronic inflammatory infiltrates (CII) type IV are the most common non-cancer diagnosis of the prostate after biopsy. Objective: To evaluate associations of both PV index (PVI), i.e. the ratio of transitional zone volume (TZV) to peripheral zone volume (PZV), and CII with PCA in patients undergoing biopsy. Subjects and Methods: Between January 2007 and Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 24 publications
2
28
0
2
Order By: Relevance
“…As a result, the risk of detecting PCA is increased when PVI ≤ 1 and decreased when PVI >1 according to the pattern of designed anatomical model [9] . CII = Chronic inflammatory infiltrate; GA = glandular atrophia; ASAP = atypical small acinar cell proliferation; HGPIN = high grade prostate intraepithelial neoplasia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the risk of detecting PCA is increased when PVI ≤ 1 and decreased when PVI >1 according to the pattern of designed anatomical model [9] . CII = Chronic inflammatory infiltrate; GA = glandular atrophia; ASAP = atypical small acinar cell proliferation; HGPIN = high grade prostate intraepithelial neoplasia.…”
Section: Resultsmentioning
confidence: 99%
“…In patients undergoing biopsy after prostate assessment, we have investigated on associations of PV index (PVI), defined as the ratio of the volume of the transitional zone (TZV) to the volume of the peripheral zone (PZV), with the risk of PCA [9] . It has been shown that PVI associated with a decreased risk of PCA and the odds of detecting PCA was almost two and half times higher in patients with a PVI ≤ 1.0.…”
Section: Introductionmentioning
confidence: 99%
“…Second, it was not evaluated whether the PSAD because tumor volume was not significantly associated with upgrading. Indeed, patients with low-grade disease at biopsy tended to have larger prostates [30]. Third, we did not evaluate the role of re-biopsy on tumor upgrading.…”
Section: Discussionmentioning
confidence: 99%
“…Total volume of the prostate (TPV) was measured by transrectal ultrasound (TRUS) by using the formula for an ellipsoid, which was transformed into volume (mL). Random 14 cores were taken by TRUS trans-perineum technique [6]. …”
Section: Methodsmentioning
confidence: 99%
“…Because of the aim of the study, features iii, iv, vi, vii were not considered by the present analysis. In each core, PCI was evaluated according to standard reported criteria [5, 6]. …”
Section: Methodsmentioning
confidence: 99%